La Corte Internacional de Justicia en el diferendo entre Perú y Chile - Méndez Chang, Elvira (2014)
This paper analyses the international obligation of solving disputes peacefully and the International Court of Justice role as a jurisdictional means of the United Nations in solving disputes. From this point, it analyses the Court role in the last years and its work solving territorial and maritime disputes, for example, the one between Peru and Chile. It presents an interesting study of the international obligations that led Peru and Chile solve the dispute peacefully and the advantages and disadvantages of it. Finally, it presents the main challenges that arise from turning to the International Court of Justice.